2017
DOI: 10.1111/sltb.12373
|View full text |Cite
|
Sign up to set email alerts
|

An Ecological Investigation of the Emotional Context Surrounding Nonsuicidal Self‐Injurious Thoughts and Behaviors in Adolescents and Young Adults

Abstract: Ecological momentary assessment (EMA) methodology was used to examine the emotional context of nonsuicidal self-injury (NSSI). Forty-seven adolescents and young adults used a novel smartphone app to monitor their emotional experiences, NSSI thoughts, and NSSI behaviors for 2 weeks. Momentary changes in both negative and positive emotions predicted greater intensity of NSSI thoughts at the subsequent assessment, while only increases in negative emotion predicted NSSI behaviors. Immediately following NSSI behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 31 publications
10
59
0
Order By: Relevance
“…One consistent finding across studies is that negative affect increases prior to NSSI (36)(37)(38), and predicts a higher probability of NSSI in the next hours (39)(40)(41)(42). For instance, using ecological momentary assessment, Kranzler and colleagues observed that a momentary increase in negative affect positively predicted NSSI in the following 2-3 hours for adolescents and young adults (40). Similarly, Houben and colleagues, demonstrated that higher-than-usual negative affect increased the likelihood of NSSI in the next 30-120 minutes among a sample of inpatients (39).…”
Section: Affective Disturbances and Nssimentioning
confidence: 84%
See 3 more Smart Citations
“…One consistent finding across studies is that negative affect increases prior to NSSI (36)(37)(38), and predicts a higher probability of NSSI in the next hours (39)(40)(41)(42). For instance, using ecological momentary assessment, Kranzler and colleagues observed that a momentary increase in negative affect positively predicted NSSI in the following 2-3 hours for adolescents and young adults (40). Similarly, Houben and colleagues, demonstrated that higher-than-usual negative affect increased the likelihood of NSSI in the next 30-120 minutes among a sample of inpatients (39).…”
Section: Affective Disturbances and Nssimentioning
confidence: 84%
“…Of note, more research is warranted investigating the potential utility of positive affect as a protective factor against NSSI, as evidence to date has yielded inconclusive results. While some researchers have observed a decrease in positive affect in the hours prior to engagement in NSSI (36,37), others failed to confirm such a time trend (38), and found that lower-than-usual positive affect is not prospectively predictive of NSSI (39,40). It may be that momentary lowered positive affect is more tolerable than increased negative affect, and therefore less relevant in eliciting NSSI (40).…”
Section: Affective Disturbances and Nssimentioning
confidence: 98%
See 2 more Smart Citations
“…In such clinical samples, the process of recruitment is slightly different. In these seven studies (Andrewes et al., 2017a; Bray et al., ; Kolar et al., ; Kranzler et al., ; Rauschenberg et al., ; Ross et al., ; Wallace et al., ), all clinical samples were recruited through clinical institutions such as mental health care institutions, health clinics, and hospitals, sometimes with additional measures such as flyers or advertisements (Kranzler et al., ; Wallace et al., ). As with schools, a strong alliance between the researcher and the institution is essential for success.…”
Section: Methodsmentioning
confidence: 99%